СЕЙСМОГРАВИТАЦИОННЫЕ ПАЛЕОДИСЛОКАЦИИ В ДОЛИНЕ РЕКИ ЧАГАН (ЮГО-ВОСТОЧНЫЙ АЛТАЙ) - Агатова А.Р.; Непоп Р.К.; Высоцкий Е.М. (My University, 2006)
The investigation of large landslides and rock-falls in Chagan-river valley along with the seismic microdeforma-tions of glacial sediments in Chagan section prove seismic activity of SE Altai in the Pleistocene-Holocene. Magnitude of paleoearthquake which caused the largest landslide in the left wall of Chagan-river valley is estimated together with the total volume of material displaced in this part of the valley by the whole Holocene seismic activity.
Keywords: Кайнозой::Четвертичная::Голоцен; Кайнозой::Четвертичная::Плейстоцен